Combining ability studies in multiple cross derivatives of upland cotton (Gossypium hirsutum) for identifying desirable plant types suitable to High Density Planting System - MURTHY, K G K; PRADEEP, T; KRISHNA, K V RADHA; REDDY, S SOKKA; NAIK, D SAIDA; CHANDRA, B SATISH (The Indian Journal of Agricultural Sciences, 2018)
To develop genotypes suitable for High Density Planting System (HDPS), six lines and seven testers that possessed compact plant type characteristics were crossed in Line × Tester mating design and the resulting 42 crosses along with their parents were evaluated at three different locations during kharif, 2014 to identify good general and specific combiners for plant type suitable for HDPS with desirable fibre quality. The results revealed significant differences among lines, testers and crosses for most of the traits and preponderance of non-additive gene action. Three lines MC 17-6, MC 16-3, MC 4-3 and two testers NH 630, MC 19-2 exhibited good gca and were found to possess compact plant type characteristics with desirable fibre quality. Among the 42 cross combinations, three crosses MC 9-1 × NH 630, MC 17-6 × MC 19-2 and MC 4-3 × MC 3-2 were identified as best specific combiners. The superior multiple cross derivatives and cross combinations can be used for developing hybrids suitable for high density planting system through heterosis breeding.